2020
DOI: 10.3390/ani10030396
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study: Antibiotic Resistance Patterns of Escherichia coli and Enterococcus Species from Wildlife Species Subjected to Supplementary Feeding on Various South African Farms

Abstract: Studies have shown that antibiotic resistance among wild animals is becoming a public health concern, owing to increased contact and co-habitation with domestic animals that, in turn, results in increased human contact, indirectly and directly. This type of farming practice intensifies the likelihood of antibiotic resistant traits in microorganisms transferring between ecosystems which are linked via various transfer vectors, such as rivers and birds. This study aimed to determine whether the practice of wildl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…coli as a model to determine levels of resistance and sensitivity of the microorganism against the active mixture of nisin/Na-EDTA. In this case, they were compared with the ampicillin (20 mcg; halo ≤13mm resistant; halo ≥17 susceptible), ceftazidime (30 mcg; halo ≤17mm resistant; halo ≥21mm susceptible), and tetracycline (25 mcg; halo ≤11mm resistant; ≥15mm susceptible) antibiotics [ 34 , 35 ]. Despite presenting inhibition halos, these are not sufficient to generate susceptibility in the target microorganism.…”
Section: Resultsmentioning
confidence: 99%
“…coli as a model to determine levels of resistance and sensitivity of the microorganism against the active mixture of nisin/Na-EDTA. In this case, they were compared with the ampicillin (20 mcg; halo ≤13mm resistant; halo ≥17 susceptible), ceftazidime (30 mcg; halo ≤17mm resistant; halo ≥21mm susceptible), and tetracycline (25 mcg; halo ≤11mm resistant; ≥15mm susceptible) antibiotics [ 34 , 35 ]. Despite presenting inhibition halos, these are not sufficient to generate susceptibility in the target microorganism.…”
Section: Resultsmentioning
confidence: 99%
“…The actual source of tetracycline resistance remains questionable, but these animals could have acquired tetracycline resistance from direct contact with sewage, carcasses or animal manure. 13,56,57 Enterococci are ubiquitously distributed in the environment 57 ;…”
Section: Discussionmentioning
confidence: 99%
“…they inhabit the gastrointestinal tract of animals as commensals. 9,49,56,58 49 The mechanisms of tetracycline resistance in these enterococci were attributed to ribosomal and efflux resistance. 3,47 The findings of this systematic review indicated that some tetracycline-resistant enterococci harboured mixed genes encoding for the ribosomal and efflux resistance of tetracycline, such as tet(M + L).…”
Section: Discussionmentioning
confidence: 99%
“…All reactions were performed in duplicate. The primers and reaction conditions used in this study are described by van den Honert et al (2020) , except the bla Z gene, which is the most common gene encoding production of beta-lactamases to hydrolyse penicillin. The bla Z gene was detected using the following primers and reaction conditions: forward primer sequence: 5’-AAGAGATTTGCCTATGCTTC-3’, reverse primer sequence: 5’-GCTTGACCACTTTTATCAGC-3’; 5 min initial denaturation at 94°C followed by 35 cycles of 94°C for 30s, 55°C for 30s and 72°C for 10 min and a final extension step of 72°C for 10 min ( Russi et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%